2019
DOI: 10.12998/wjcc.v7.i16.2256
|View full text |Cite
|
Sign up to set email alerts
|

Hypoallergenicity of a thickened hydrolyzed formula in children with cow’s milk allergy

Abstract: BACKGROUND Allergy to cow’s milk is the most frequent allergy occurring in infants and young children. The dietary management of these patients consists of the elimination of any cow’s milk proteins from the diet, and for formula-fed infants, the substitution of the usual infant formula with an adapted formula that is generally based on extensively hydrolyzed cow’s milk proteins. The American Academy of Pediatrics has established specific criteria to confirm the hypoallergenicity of a formula inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Five studies reported use of CoMiSS™ as an outcome measure (see Table 4). 27–31 In all studies, after symptomatic infants were administered cow's milk‐free formula, there was a significant change in CoMiSS™ score, but no minimally important difference has been established.…”
Section: Resultsmentioning
confidence: 98%
“…Five studies reported use of CoMiSS™ as an outcome measure (see Table 4). 27–31 In all studies, after symptomatic infants were administered cow's milk‐free formula, there was a significant change in CoMiSS™ score, but no minimally important difference has been established.…”
Section: Resultsmentioning
confidence: 98%
“…In the studies by Dupont et al, Fierro et al, and Rossetti et al, the authors used CoMiSS as a tracking tool to demonstrate the stable low CoMiSS after introducing the new test formula in infants already diagnosed with CMA responding to an elimination diet [ 20 , 24 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review by Thompson et al [ 40 ], including 15 diagnostic-accuracy studies [ 14 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 42 ], considered that there is no well-defined diagnostic role for symptom-based scores, including CoMiSS, and that current estimates of their accuracy should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
“…There are now thickened casein-based EHF and AAF with proven hypoallergenicity suitable for these patients available in some countries. [89][90][91][92] The studies by Dupont et al 91,93 and Vandenplas et al 90 To determine cow's milk tolerance in clinical practice, tolerance development may be indicated by a child tolerating milk in small quantities, baked or probably also in some fermented forms Heine 71 Milk avoided and substituted with hypoallergenic formula or maternal exclusion and sleeping time. In children that had challenge positive CMA, both thickened and un-thickened extensive hydrolysates were equally tolerated and for those that were challenge positive, a thickened hydrolysate had a significantly better impact than a non-thickened hydrolysate.…”
Section: Formul a S For Cma In The Manag Ement Of G Ordmentioning
confidence: 99%
“… 88 However, none of the current guidelines on CMA, cover hypoallergenic formulas that have specifically been designed for GORD. There are now thickened casein‐based EHF and AAF with proven hypoallergenicity suitable for these patients available in some countries 89‐92 . The studies by Dupont et al 91,93 and Vandenplas et al 90 also assessed regurgitation episodes, crying and sleeping time.…”
Section: Formulas For Cma In the Management Of Gordmentioning
confidence: 99%